2022
DOI: 10.1039/d1qi01077h
|View full text |Cite
|
Sign up to set email alerts
|

Mo6+–P5+ co-doped Li2ZnTi3O8 anode for Li-storage in a wide temperature range and applications in LiNi0.5Mn1.5O4/Li2ZnTi3O8 full cells

Abstract: One-step solid-state method has been used to synthesize Li2ZnTi3O8 (LZTO) co-doped by Mo6+ and P5+ ions (LZM7TP3O). The structure stability, pore size and specific surface area have been improved via...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…The selection of the potential range for the full cells is based on our previous work. 28 Based on the active mass of LZTO-FA, the initial discharge specific capacity reaches 207.1 mA h g −1 , and a discharge specific energy of 673.5 W h kg −1 is produced for the LiNi 0.5 Mn 1.5 O 4 /LZTO-FA full cell (Fig. 8e and f ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The selection of the potential range for the full cells is based on our previous work. 28 Based on the active mass of LZTO-FA, the initial discharge specific capacity reaches 207.1 mA h g −1 , and a discharge specific energy of 673.5 W h kg −1 is produced for the LiNi 0.5 Mn 1.5 O 4 /LZTO-FA full cell (Fig. 8e and f ).…”
Section: Resultsmentioning
confidence: 98%
“…It is reported that the initial CE can be improved via doping or coating, which can reduce the side reactions between LZTO and the electrolyte. 28,30 When the current density is up to 2 A g −1 , LZTO-FA still has good cycling performance. After 400 cycles, no capacity decays based on the 2nd cycle as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Following previous reports on cyclic divalent species, [20][21][22][23][24][25][26][27][28] organic compounds and nanostructures, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] now we compare and contrast new rNHGes (1-10) by fusion of one benzene, pyrrole, phosphole, furan and thiophene ring in "orthoor zigzag" arrangement and "paraor chair" arrangement to 1H-4-germapyridine-4-ylidene (1) as the reference germylene.…”
Section: Methodsmentioning
confidence: 88%
“…Besides, another approach for high-performance RMBs is to find alternative anode materials beyond Mg metal so that the problem of electrolyte compatibility could be solved. Although graphite is commercialized as anode for LIBs, [90,91] it is difficult to be intercalated with Mg ions, mainly owing to the high ionization potential of Mg (7.65 eV) than that of Li (5.39 eV). Alternative intercalation-type anode materials such as TiO 2 -B, [92][93][94] Li 4 Ti 5 O 12 , [95] Na 2 Ti 3 O 7 , [96][97][98] and Li 3 VO 4 [96] have been experimentally demonstrated to reversibly intercalate Mg ions; however, their diffusion kinetics are sluggish due to the strong electrostatic interaction.…”
Section: Conventional Rmbsmentioning
confidence: 99%